Digitalized bite mark analysis for the undergraduate dental students / Mohd Yusmiaidil Putera Mohd Yusof - Mohd Yusof, Mohd Yusmiaidil Putera (Faculty of Dentistry, 2015)
In legal system, the admissibility of bite mark injury has proven to give more positive impact when current technologies are adapted to its analysis. The early exposure of the digitalized bite mark analysis during the undergraduate dental program is beneficial to stimulate interests and provide guidance among the professional dentists. The step-by-step bite mark analysis partly adapted from KU Leuven, Belgium is emphasized by delivering the illustrated practical techniques using computer software Adobe Photoshop®. The overlays analysis demonstrated its practicality as easy to use and offered opportunities to learn through unconventional mode of teaching. The incorporation of bite mark injury analysis to the undergraduate dental learning is highly recommended.